Data-driven reaction coordinate discovery in overdamped and non-conservative systems: application to optical matter structural isomerization - Shiqi Chen (Nature Portfolio, 2021)
Optical matter consisting of nanoparticle constituents in solution is of key interest due to the exhibited self-assembling mechanisms. The authors propose a principal components analysis based data-driven approach to determine the collective modes of colloidal clusters mimicking optical binding used in colloidal self-assembly.